انعكاسات القطاع غير الرسمي على الاقتصاد الجزائري - بن سمينة, د/ دلال (Sciences humaines, 2016)
شهد القطاع غير الرسمي في الجزائر تطورا متزامنا مع المرحلة الانتقالية للاقتصاد الوطني، ويشكل حاليا أكثر من ثلث الناتج الوطني، وينجم عن تنامي هذا القطاع ضياع جزء كبير من إيرادات الخزانة العامة للدولة، كما يشكل خطورة على القطاع الرسمي ويؤثر بشكل واضح على صحة البيانات المتعلقة بالمؤشرات الاقتصادية، وفي المقابل وحسب العديد من الاقتصاديين يعد هذا القطاع بديلا وقت الأزمات ومصدر مهم للطبقة الفقيرة.          وقد حاولنا من خلال هذه الورقة البحثية تسليط الضوء على واقع القطاع غير الرسمي في الجزائر والتعرض لأهم الانعكاسات التي يخلفها  نمو هذا القطاع على الاقتصاد الوطني. The informal sector in Algeria developed in sync with the transitional phase of the national economy, currently represents more than one-third of national output,  resulting from the growth of this sector, the loss of a large portion of the revenue the State Treasury and constitutes a danger to the formal sectors, also affects clearly on the validity of the data relating to economic indicators, on the other hand, according to many economists, this sector substitute a time of crisis and an important source of poor layer.             We have tried through this paper to shed light on the reality of the informal sector in Algeria and exposure to the most important repercussions left by the activity of this sector to the national economy.